Realism, physical meaningfulness, and molecular spectroscopy - Miyake, Teru (Oxford University Press, 2023)
Although the realism debate has focused on the work of Jean Perrin on Brownian motion, we claim that the best place to look for a resolution of this debate is the period after the late 1920s, when stable theory-mediated measurement of molecular parameters first became possible through the application of quantum mechanics to spectroscopy. This paper first examines how stable measurement of the molecular parameters of diatomic molecules was achieved in spectroscopy, and then gauges what evidence there is that this stable measurement is giving spectroscopists access to the real properties and structure of molecules. We argue that an evaluation of the latter question requires a distinction to be made between physically meaningful representations and those that are not, and a full answer requires the deployment of that distinction in the analysis of scientific research on atoms and molecules in the period after 1950.